Fishing Quota and International Obligation: Why Has Indonesia been Indicated as a Non-Compliant State - Indriyani, Rachma; Rahim, Asmar Abdul; Azmi, Ruzita (Faculty of Law, Hasanuddin University, 2021)
Indonesia committed to conserving the tuna resources by participating in some RFMOs. From all regional organizations where Indonesia has been joined, the CCSBT is the unique one, due to it governs a single tuna species, which is called Southern Bluefin Tuna. This kind of tuna is essential for Indonesia because it is the world’s most expensive tuna and SBT migrates through Indonesian fisheries management zones and goes even further within the territorial waters, where the SBT spawning area is located. This natural characteristic distinguishes Indonesia from other Parties to CCSBT. Nevertheless, the Country has been dealing with its obligation to comply with national quota allocation. For some fishing season periods, the CCSBT indicated Indonesia as a non-compliant. By applying the qualitative approach, this study considers how Indonesia’s non-compliance has been addressed in fishing for shared fish stocks. The data collection was conducted through semi-structured interviews and legal analysis of law and policy instruments. This method leads the elaboration to reveal domestic factors affecting non-compliance by Indonesia. This study argues, the fisheries legislation should consider the provision concerning fishing for resources under quota system, hence, it will provide sufficient legal base to take enforcement measures towards non-compliance with fishing quota.